Synthesis and electrochemical properties of new cobalt and manganese phthalocyanine complexes tetra-substituted with 3,4-(methylendioxy)-phenoxy - Erdogmus, Ali; Akinbulu, Isaac Adebayo; Nyokong, Tebello (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
The synthesis and electrochemical properties of new cobalt and manganese phthalocyanine complexes, tetra-substituted with 3,4-(methylendioxy)-phenoxy at the peripheral (complexes 3 and 5) and non-peripheral (complexes 4 and 6) positions, are reported. Complexes 3 and 4 showed Q-band absorption, in DMF, at 668 and 686 nm, respectively while Q-band due to complexes 5 and 6 appeared at 732 and 760 nm, respectively in CHCl(3). All the complexes showed well resolved redox processes attributed to both metal and ring based processes. Complexes 3 and 4 showed four redox processes, labeled I, II, III and IV. For complex 3, process I (Co(I)Pc(-2)/Co(I)Pc(-3)) was observed at -1.45 V. II (Co(II)Pc(-2)/Co(I)Pc(-2)) at 0.38 V. III (Co(III)Pc(-2)/Co(II)Pc(-2)) at +0.49 V and IV (Co(III)Pc(-1)/Co(III)Pc(-2)) at +0.97 V versus Ag vertical bar AgCl. Similar processes were observed for complex 4 at -1.36 V. -0.27 V. +0.56 V. +1.03 V versus Ag vertical bar AgCl, respectively. Complexes 5 and 6 showed two redox processes (I and II). For complex 5, these processes appeared at -0.79 V (Mn(II)Pc(-2)/Mn(II)Pc(-3), I) and -0.07 V versus Ag vertical bar AgCl (Mn(III)Pc(-2)/Mn(II)Pc(-2), II), while for complex 6, they were observed at -0.86 V and -0.04 V versus Ag vertical bar AgCl. Spectroelectrochemistry was used to probe and confirm the origin of these processes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cobalt; Manganese; 3,4-(Methylendioxy)-phenoxy phthalocyanine; Cyclic voltammetry; Spectroelectrochemistry; ELECTROCATALYTIC ACTIVITY; CARBON NANOTUBES; ELECTRODES; OXIDATION; POLYMER; Chemistry; Crystallography